Quality improvement in the surgery-related processes: Managerial challenges and solutions from hospitals of Iran - Tina Beyranvand; Aidin Aryankhesal; Asgar Aghaei Hashjin (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: There is a growing global movement toward quality and safety in healthcare and quality improvement (QI) in general surgery. The first step in any QI initiative is identifying the challenges and barriers to achieve such goals and then to define appropriate actions. This study aims to provide an overview of the QI challenges in Iranian hospitals' surgery-related processes and suggest applied solutions accordingly. METHODS: This is a sequential (qual-quant) mixed-method study from November 2019 to January 2020, involving 21 face-to-face interviews with hospital managers, quality officers, and surgery-related clinicians and staff, followed by a Delphi consensus-seeking stage to finalize solutions. MAXQDA software was applied for organizing the concepts, and thematic content analysis was used for analyzing the data as an inductive approach to extract the emerging themes and sub-themes. RESULTS: The managerial problems were classified into four groups of (I) defects and delays in completing patient medical records, (II) irregularity and the lack of transparency in the direction of processes in the hospital, (III) inappropriate and unrealistic operating scheduling, and (IV) poor safety considerations. The proposed solutions included imposing stricter regulations for competing for medical records, such as reduction of payments, development of guiding brochures or protocols for patients on their arrival, assigning a certain number of experienced nurses and surgeons for schedule management, rewarding the report of medical and surgical error cases, and developing a regular monitoring program for the proper implementation of surgical safety guidelines. CONCLUSION: There are various managerial barriers that hamper QI in hospitals' surgery-related processes. Implementing simple but agreed solutions can lead to saving patients' lives, reduction of the unnecessary use of resources, and enhance of patient and staff satisfaction.